An investigation of gear meshing behaviour of planetary gear systems for improved fault diagnosis - Xue, Song (Curtin University, 2016)
This research has presented gear dynamic models and associated simulations to improve gear fault detection. These models include the use of finite element and lumped parameter methods for both fixed axis and planetary gear systems. The findings in this research provide an improved understanding of the gear fault mechanism and advance the gear fault detection capability of the whole drive train system. It also suggests further effective ways of monitoring the whole gear train system.